1998
DOI: 10.1172/jci1174
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori upregulates expression of epidermal growth factor-related peptides, but inhibits their proliferative effect in MKN 28 gastric mucosal cells.

Abstract: Acute exposure to Helicobacter pylori causes cell damage and impairs the processes of cell migration and proliferation in cultured gastric mucosal cells in vitro. EGF-related growth factors play a major role in protecting gastric mucosa against injury, and are involved in the process of gastric mucosal healing. We therefore studied the acute effect of H. pylori on expression of EGF-related growth factors and the proliferative response to these factors in gastric mucosal cells (MKN 28) derived from gastric aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 49 publications
(35 reference statements)
7
57
2
Order By: Relevance
“…Furthermore, Mycobacterium avium infection of macrophages down-regulates IFN-␥ receptor 1 and 2 protein expression (42), and Porphyromonas gingivalis outer membrane vesicles decrease the expression and activity levels of Jak1 and Jak2 in endothelial cells (43). In contrast, in this study we found that H. pylori infection did not decrease the protein expression levels of IL-4R␣ or Jak1, similar to its suppression of EGFrelated peptide signaling in MKN28 gastric mucosal cells without affecting EGF receptor expression (44). Because suppression of IL-4-induced Stat6 activation was time-dependent, it may suggest that induction of epithelial cell signal transduction and gene transcription are important here.…”
Section: H Pylori Infection Does Not Alter Expression Of Either Il-4contrasting
confidence: 50%
“…Furthermore, Mycobacterium avium infection of macrophages down-regulates IFN-␥ receptor 1 and 2 protein expression (42), and Porphyromonas gingivalis outer membrane vesicles decrease the expression and activity levels of Jak1 and Jak2 in endothelial cells (43). In contrast, in this study we found that H. pylori infection did not decrease the protein expression levels of IL-4R␣ or Jak1, similar to its suppression of EGFrelated peptide signaling in MKN28 gastric mucosal cells without affecting EGF receptor expression (44). Because suppression of IL-4-induced Stat6 activation was time-dependent, it may suggest that induction of epithelial cell signal transduction and gene transcription are important here.…”
Section: H Pylori Infection Does Not Alter Expression Of Either Il-4contrasting
confidence: 50%
“…Pai et al (1998) showed that H. pylori culture supernatants from VacA strains, but not VacA À strains, inhibited EGFmediated EGFr upregulation and phosphorylation, suggesting that the growth-inhibitory effect is at the level of receptor activation (Pai et al, 1998). On the other hand, Romano et al (1998b) showed that H. pylori broth culture ®ltrates did not affect EGFr phosphorylation by EGFrelated growth factors, while they inhibited EGF-related peptide-dependent increase in cell proliferation, thus suggesting a downstream block to the activation of the receptor. This effect did not seem to be mediated by several known virulence factors, but was dependent on the release of a low (< 12 kDa) molecular mass component (Romano et al, 1998b).…”
Section: Host Response To H Pylori-induced Cell Damagementioning
confidence: 95%
“…On the other hand, Romano et al (1998b) showed that H. pylori broth culture ®ltrates did not affect EGFr phosphorylation by EGFrelated growth factors, while they inhibited EGF-related peptide-dependent increase in cell proliferation, thus suggesting a downstream block to the activation of the receptor. This effect did not seem to be mediated by several known virulence factors, but was dependent on the release of a low (< 12 kDa) molecular mass component (Romano et al, 1998b). A possible explanation for the apparent discrepancy between in vivo and in vitro studies evaluating the effect of H. pylori on gastric cell proliferation might be that in vivo studies are representative of the effect of persistent H. pylori infection, whereas in vitro experimental studies are representative of an acute H. pylori-mediated effect.…”
Section: Host Response To H Pylori-induced Cell Damagementioning
confidence: 95%
See 1 more Smart Citation
“…While abl and src non-receptor tyrosine kinases are expressed in all gastric cell lines and cancer tissues examined, the src protein levels do not re¯ect activation status (kinase activity) (O'Neill et al, 1997;Takaishi et al, 2000). It is worth noting that H. pylori, an infectious pathogen, can up-regulate tyrosine kinase signal transduction pathways including src, EGFR, erbB2, MAPK and MKK4, following infection (Elitsur et al, 1999;Haruma et al, 2000;Meyer-Ter-Vehn et al, 2000;Naumann et al, 1999;Romano et al, 1998). Recently, H. pylori infection has been linked to peptic ulcer disease and gastric adenocarcinoma formation (EUROGAST Study Group, 1993;Segal et al, 1997;Kuniyasu et al, 2000).…”
Section: Other Protein Tyrosine Kinases In Gastric Cancermentioning
confidence: 99%